Analisis Pengembangan Sektor Pariwisata di Kota Padang - Novi Yanti (Journal of Economics and Management Scienties, 2022)
The purpose of this study is to know: a) how the development of tourism sector in the city of padang, b) what development programs undertaken by the cultural and tourism office of the city of padang, and c) obstacles faced by the culture and tourism office of the city of padang in developing tourism object . Technique of collecting data in this research is done by interview, observation also literature study. The analytical method used is descriptive qualitative analysis that is digging information from the source about the development of tourism sector in Padang city. The results showed that a) Tourism sector in the city of Padang has experienced a good development. This is evident from the increase in the number of visitors who come to the tourist attraction of the city of Padang, especially Padang Beach attractions and Sweet water Beach has become a favorite tourist destination for local and foreign tourists. In addition, the municipal government of Padang together with the tourism office also continues to make development efforts by revitalizing the 5 selected tourist objects, namely padang beach, siti nurbaya, heritage, old town, and waterfront, b) development program undertaken by the culture and tourism office the city of Padang through various activities such as tourism destination development programs, partnership development, regional tourism product development, promotion of tourism in social media sharing and web, c) Constraints faced in the development of urban tourist attraction is limited budget funds, community mindset is still primitive and yet modern, the education of the tourism actors is still low and not well managed infrastructure in some tourist attractions such as beaches sweet water, sand jambak and others.